Lipopolysaccharide pretreatment inhibits oxidative stress-induced endothelial progenitor cell apoptosis via a TLR4-mediated PI3K/Akt/ NF-ÎºB p65 signaling pathway - Wang, Meihui; Xia, Liang; Fu, Guosheng (Cellular and Molecular Biology, 2019)
Endothelial progenitor cells (EPCs) improve neovascularization and endothelium regeneration. Transplantation with EPCs is a therapeutic strategy for the treatment of ischemic diseases. However, the transplanted EPCs are susceptible to adverse environments such as hypoxia, inflammation and oxidative stress. Oxidative stress-induced apoptosis of transplanted EPCs greatly reduces their therapeutic efficacy. Lipopolysaccharide (LPS) is a highly immunogenic antigen. Recent findings suggest that low dose of LPS pretreatment has protective effect against apoptosis. In this study, the role of LPS in apoptosis of EPCs was investigated. Pretreatment with 1µg/ml LPS prevented oxidative stress-induced EPCs apoptosis and ROS generation, which effects were abolished by TAK-242, a specific TLR4 antagonist. Further investigation of the mechanisms demonstrated that the activation was mediated by TLR4, and that PI3K/Akt/ NF-ÎºB p65 signaling pathway may play a critical role in the process.